Neoliberalism and its impact on English as a medium of instruction in Malaysia, Thailand and Vietnam / Nurul Farehah Mohamad Uri and Mohd Salehhuddin Abd Aziz - Mohamad Uri, Nurul Farehah; Abd Aziz, Mohd Salehhuddin (Universiti Teknologi MARA Cawangan Kedah, 2018)
In today's modern world economy, there is always a competition among countries as a consequence of globalization. A salient feature of globalization is the adoption of neoliberalism - a modern contemporary economic ideology. Neoliberalism ideology is spreading fast around the globe including in South East Asia. The spread and adoption of English as the main medium of communication in conducting business, trade, commerce and various fields is the direct and indirect results of the impact of neoliberalism. This ideology has brought about many changes economically, socially and educationally to these countries. This paper intends to investigate the impact of neoliberalism especially on English as a medium of instruction in Malaysia, Thailand and Vietnam. It will focus on the implementation of CEFR which is also directly related to the adoption of neoliberalism.